2021
DOI: 10.3390/su13020922
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Ecosystem on the Motivation of Social Entrepreneurs

Abstract: Social entrepreneurs have particular characteristics that differentiate them from commercial entrepreneurs, but research on this differential behavior is still a field in which many questions need to be explored. Specifically, a factor of special relevance is the ecosystem where social entrepreneurial activity takes place. The aim of this study is to analyze how the ecosystem affects the motivation of social entrepreneurs compared to commercial entrepreneurs. This general objective is divided into two specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Carriles-Alberdi et al analyzed the influence of the entrepreneurial ecosystem and highlighted important aspects, namely that people with higher education have a greater inclination towards entrepreneurship. The authors also found that in countries based on innovation, women are more easily incorporated into the entrepreneurial phenomenon [16]. Also, a large part of potential entrepreneurs never starts entrepreneurial activity, or shortly after starting their business, they abandon it.…”
Section: Analysis Of the Entrepreneurial Ecosystemmentioning
confidence: 92%
“…Carriles-Alberdi et al analyzed the influence of the entrepreneurial ecosystem and highlighted important aspects, namely that people with higher education have a greater inclination towards entrepreneurship. The authors also found that in countries based on innovation, women are more easily incorporated into the entrepreneurial phenomenon [16]. Also, a large part of potential entrepreneurs never starts entrepreneurial activity, or shortly after starting their business, they abandon it.…”
Section: Analysis Of the Entrepreneurial Ecosystemmentioning
confidence: 92%
“…Studies from the sub‐theme social enterprise formation find that although many specific financing options for social enterprises have recently been established, social entrepreneurs still have fewer financing options than regular entrepreneurs, especially in the early start‐up stage (Carriles‐Alberdi et al., 2021; Harding, 2007; Hoogendoorn et al., 2019). This lack of financial support not only prevents social entrepreneurs from starting social enterprises, but also influences their decisions, for example, whether to choose a for‐profit or non‐profit legal form (Child et al., 2015; Stirzaker et al., 2021).…”
Section: Descriptive Findings: Mapping a Diversified Landscapementioning
confidence: 99%
“…On the one hand, researchers argue that a strong economy dominated by market logics and functioning traditional financial markets facilitates private investments in social enterprises (Kistruck et al., 2011; Popov et al., 2018; Zhao & Lounsbury, 2016). On the other hand, studies find that exactly such markets are not beneficial for social enterprises (Carriles‐Alberdi et al., 2021; Cobb et al., 2016; Mendoza‐Abarca et al., 2015).…”
Section: Descriptive Findings: Mapping a Diversified Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…They did do by becoming part of an entrepreneurial ecosystem connecting global designers and fabricators through digital networks. Second, their network formation in a disembedded space, united only by a sense of the social value that they could contribute through the ecosystem they were forming (Carriles‐Alberdi et al, 2021 ), was also entrepreneurial. Finally, they were entrepreneurs in the Schumpeterian sense of social engineering identified by Zahra et al ( 2009 ).…”
Section: Introductionmentioning
confidence: 99%